2019
DOI: 10.1111/tbj.13196
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of gabapentin for the prevention of paclitaxel induced peripheral neuropathy: A randomized placebo controlled clinical trial

Abstract: Neuropathy is a dose limiting side effect of taxanes which may impact the quality of life and treatment outcomes. This randomized placebo‐controlled double‐blinded clinical trial was carried out to assess the efficacy of gabapentin in preventing chemotherapy induced neuropathy. Women with breast cancer were randomized into two groups of paclitaxel chemotherapy with gabapentin 300 mg/three times a day orally or placebo for 2 weeks started at day 1 of each paclitaxel cycle. Two groups were compared based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…Agents benefitting diabetic peripheral neuropathic pain are often ineffective against CIPN, implicating different disease mechanisms in case of these two peripheral neuropathies ( Frampton and Foster, 2006 ; Finnerup et al, 2010 ; Mishra et al, 2012 ). However, out of pregabalin and gabapentin, approved by the Food and Drug Administration (FDA) for the first-line treatment of diabetic neuropathic pain, gabapentin has been found to be effective against PTX-induced peripheral neuropathy in a recent randomized clinical trial ( Aghili et al, 2018 ) Both these drugs are well tolerated, although somnolence and dizziness are most common side effects. Peripheral edema, weight gain, nausea, vertigo, asthenia, dry mouth, and ataxia are some other side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Agents benefitting diabetic peripheral neuropathic pain are often ineffective against CIPN, implicating different disease mechanisms in case of these two peripheral neuropathies ( Frampton and Foster, 2006 ; Finnerup et al, 2010 ; Mishra et al, 2012 ). However, out of pregabalin and gabapentin, approved by the Food and Drug Administration (FDA) for the first-line treatment of diabetic neuropathic pain, gabapentin has been found to be effective against PTX-induced peripheral neuropathy in a recent randomized clinical trial ( Aghili et al, 2018 ) Both these drugs are well tolerated, although somnolence and dizziness are most common side effects. Peripheral edema, weight gain, nausea, vertigo, asthenia, dry mouth, and ataxia are some other side effects.…”
Section: Discussionmentioning
confidence: 99%
“…10 Conversely, another placebo-controlled trial of 20 patients receiving paclitaxel demonstrated that gabapentin lowered the incidence of grade 2 or 3 neuropathy. 11 Currently, there are no non-pharmacological nor pharmacological agents recommended for the prevention of CIPN. 9 However, cryotherapy is a nonpharmacological strategy that is worth exploring further.…”
Section: Introductionmentioning
confidence: 99%
“…10 Conversely, another placebo-controlled trial of 20 patients receiving paclitaxel demonstrated that gabapentin lowered the incidence of grade 2 or 3 neuropathy. 11…”
Section: Introductionmentioning
confidence: 99%
“…The use of specific drugs to treat and, desirably, to prevent these effects is extremely important in order to offer an acceptable quality of life for the patients . Recently, Aghili and colleagues showed gabapentin, an anticonvulsant drug, may give potential benefits in the prevention of neuropathic symptoms and signs and nerve function impairment . In particular, this drug may even reduce the worsening of nerve conduction.…”
mentioning
confidence: 99%
“…Through the work by Aghili and colleagues, besides the relevant translations in clinical practice, we can infer the importance of literature review to design a proficient research study . Generally, the knowledge of the status of the art about a disease is a fundamental component of scientific work.…”
mentioning
confidence: 99%